Meningkatkan Kreativitas Seni Rupa Anak Melalui Kegiatan Mencetak dengan Bahan Alam di Paud Aisyiyah Lansano Pesisir Selatan - Adi Supriyenti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2013)
Art’s Creativity of children in early childhood Aisyiyah Lansano still relatively low, it can be seen from the initial conditions, there are still many children who have not been able to make a simple drawing, creating simple images and simple image redesign. The method used is less precise teacher, not according to the needs and development of children and the media that teachers use less attractive to be one cause of this condition. This research aims to improve child art creativity in making a simple drawing, creating simple images and simple image redesign activities in early childhood scored Aisyiyah Lansano Pesisir Selatan.  This type of research is a classroom action research, which is the subject of this research is early childhood education students Aisyiyah Lansano totaling 20 people.  The data in this study were obtained through observation, then the data is processed and analyzed with techniques percentage.  The study was conducted during two cycles, the results obtained show that through printing with natural ingredients to increase creativity of art in early childhood children Aisyiyah Lansano.  Before the researt, art skills of child are still low, but after going through the learning cycle I and II, seen an increase in child art creativity, therefore it is recommended to teachers to be more creative use of media and the schools are expected to set up infrastructure to stimulate the development of children through print activities with other natural materials